Sensibilidade da citoinclusão (PAAF) para detecção de CK5, RE e RP no carcinoma primário de mama na cadela - Silveira, Tatiany Luiza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Breast carcinoma in a dog is a disease relatively frequent in bitches of 10 years old, displays important morbidity and evolve to death. The cell block for the diagnosis of injury in women is the method of choice in the investigation, because it provides subsidies to provide for response to therapy. However, for the dog is unknown the application of this technique, therefore, this study aimed to correlate the morphological patterns of canine mammary tumors between cell block technique and surgical specimen and compare the immunohistochemical marking of ER, PR and CK5 between the two methods in 25 samples. The cell block and surgical specimens were submitted to histological processing, preparation of slides for HE and subsequent immunohistochemistry (IQ) for estrogen receptor α (ER), progesterone (PR) and cytokeratin 5 (CK5). Were considered positive for ER and PR cases where there was marking on more than 1% of neoplastic cells and for CK5 the cases where there was marking on more than 10% of neoplastic cells. The level of agreement between the cell block and the surgical specimen was 86.9% for CK5 and 82.6% for the RE. For the HE staining was 100% agreement for the diagnosis of cancer between the techniques. Immunohistochemistry showed a sensitivity of 85.71%, 95.45% and 100% and Cohen's Kappa index of 0.78, 0.84, and 0.95 for ER, PR and CK5 respectively, and 100% specificity and p <0.01 for all three markers. Therefore the citoinclusão it is an affordable method, fast and low cost, which offers high sensitivity in immunohistochemical marker and in cytomorphological diagnosis of mammary carcinoma in female dogs

O carcinoma mamário é uma doença relativamente frequente entre as cadelas na faixa etária de 10 anos e apresenta morbidade importante, com expectativa de sobrevida média de 5 anos. A citoinclusão é usada rotineiramente na Medicina como método de escolha na investigação, pela rapidez que fornece subsídios para prever a resposta terapêutica. Entretanto, para a cadela se desconhece a aplicação da tal técnica, portanto, o estudo objetivou correlacionar os padrões morfológicos dos tumores mamários caninos encontrados na técnica de citoinclusão e na análise histológica da peça cirúrgica e comparar a marcação de RE, RP e CK5 nos os dois métodos em 25 amostras de carcinoma mamário. A citoinclusão e espécime cirúrgico foram submetidos ao processamento histológico, confecção das lâminas para coloração de hematoxilina-eosina (HE) e posterior reação imunoistoquímica (IQ) para receptores de estrógeno α (RE), progesterona (RP) e citoqueratina 5 (CK5). Foram consideradas positivas as marcações das células neoplásicas acima de 1% para RE e RP, e acima de 10% para CK5. Pela coloração de HE houve 100% de concordância no diagnóstico das neoplasias entre técnica de citoinclusão e análise histopatológica. A imunoistoquímica apresentou sensibilidade de 85,71%, 95,45% e 100% e índice Kappa de Cohen de 0,78, 0,84, e 0,95 para o RE, RP e CK5 respectivamente, e 100% de especificidade e p<0,01 para os três marcadores. Portando, a citoinclusão trata-se de um método acessível, rápido e de baixo custo, que oferece alta sensibilidade no diagnóstico citomorfológico e imunoistoquímico de carcinoma mamário em cadelas
Keywords: Cão - Doenças; Cancer em cão; Estrógenos - Receptores; Progesterona; Imunohistoquímica; Immunohistochemistry; Dogs